Age differences in the association of prognostic nutritional index quartiles and heart failure in US adults: the NHANES 2011–2018 - Zhou, Jianlong; Li, Yadi; Zhu, Lv; Yue, Rensong (Frontiers in Nutrition, 2025)
BackgroundHeart failure (HF) is the leading cause of morbidity and mortality among adults worldwide. Systemic chronic inflammatory, immune dysfunction and malnutrition are considered important characteristics of HF patients. The prognostic nutritional index (PNI) is an emerging indicator for evaluating an individual's immune-inflammatory and nutritional status. However, its relationship with the prevalence of HF is unclear. This study aimed to investigate the relationship between PNI and HF.MethodsThis study included 19,965 participants from 2011 to 2018 in the National Health and Nutrition Examination Survey (NHANES) database. Weighted multiple linear regression and logistic regression, adjusted for potential confounders, were used to analyze the association between PNI and HF. Generalized additive modeling (GAM), smoothing curves, and subgroup analyses were also conducted for a deeper understanding. The diagnostic ability of the PNI for HF was assessed by analyzing the receiver operating characteristic (ROC) curve and calculating the area under the curve (AUC).ResultsUnadjusted model 1 indicated a negative association between PNI and HF risk (odds ratio (OR) = 0.90, 95% CI: 0.89, 0.92), which persisted in the fully adjusted model 3 (OR = 0.97, 95% CI: 0.95, 0.99). This suggests that each unit increase in PNI reduces the likelihood of developing HF by 3%. When continuous variables were divided into quartiles, quartile 4 had a 52% lower PNI than quartile 1 (OR = 0.48, 95% CI: 0.39, 0.56). Subgroup analyses showed a significant interaction between age and the correlation between PNI and HF (interaction P < 0.05). Among those aged 20–59 years, the risk of developing HF was reduced by 9% for each 1-unit increase in PNI. The ROC curve showed that PNI had a high diagnostic value for HF with an AUC value of 0.642.ConclusionsThe higher PNI is significantly associated with a lower prevalence of HF, particularly in the nonelderly population (20–59 years). This suggests that PNI may serve as a valuable screening tool for HF risk, emphasizing the importance of nutritional and immune status in HF development.